Republikanizm i liberalizm w świetle idei konstytucjonalizmu. Uwagi o legitymizacji prawa - Bekrycht, Tomasz (Uniwersytet im. A. Mickiewicza w Poznaniu Wydział Nauk Społecznych, Instytut Filozofii UAM, 2018)
This paper addresses two key issues. The first involves an analysis of the connections between the ideas of republicanism, liberalism and constitutionalism. The second concerns the republican idea of self-determination and, consequently, the issue of the legitimation of law. The first section of the paper puts forward the thesis that constitutionalism can nowadays be understood as the idea of the legitimization of positive law, involving the synthesis of the two key values proclaimed by republicanism and liberalism, namely self-determination and negative freedom. The issue here is that the ideas of self-determination and negative freedom are both counterfactual, and the only area in which they can be synthesized is within the conceptual framework of positive law. The second section of the paper constitutes the justification of this thesis.
Republicanism and liberalism considered with regard to idea of constitutionalism. Remarks about the legitimation of law
Keywords: legitimation of the law; republicanism; liberalism; constitutionalism